Arti Penting Pelindungan Hak Asasi Manusia bagi Pekerja Migran Indonesia - Suci Setyafani Cahyani Ginoga; Abdul Mustopa Jawahid (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
Indonesian Migrant Workers (PMI) are a group vulnerable to Human Rights violations while working abroad. This article aims to analyze the importance of human rights in protecting PMI and to review the state's obligations in fulfilling the rights of its citizens working abroad. This research uses a normative juridical method with a conceptual approach, legislation, and case studies. The research results show that the protection of PMI is not just an aspect of employment but an integral part of human rights protection. The state has the obligation to fulfill, protect, and respect every right of PMI. Although there is a legal framework through Law Number 18 of 2017, its implementation is still weak. A case study at the Immigration Detention Depot in Malaysia revealed serious human rights violations against PMI, such as torture and medical neglect. If viewed within the concept of human rights, the state is deemed to have failed in providing effective legal protection, both in prevention and recovery. Structural weaknesses were also found, such as the lack of supervision, education, and legal assistance for PMI. This research emphasizes the importance of the state's responsibility to ensure more concrete and sustainable human rights protection for migrant workers.